Pengaruh Ukuran Perusahaan, Resiko Keuangan, Kompleksitas dan Reputasi Auditor terhadap Audit Fee pada Perusahaan Sektor Kesehatan yang terdaftar di BEI Periode 2021-2024 - Putri Enjelina Sianipar; Ivo Maelina Silitonga; Rike Yolanda Panjaitan; Mulatua Silalahi (Jurnal Ilmiah Raflesia Akuntansi, 2026)
This study aims to analyze the effects of firm size, financial risk, firm complexity, and auditor reputation on audit fees for companies in the pharmaceutical subsector of the healthcare industry listed on the Indonesia Stock Exchange during the 2021–2024 period. This study employs a quantitative approach using secondary data in the form of financial statements. The sample consists of 10 companies selected via purposive sampling, resulting in a total of 40 data points. Data analysis was conducted using multiple linear regression. The results indicate that, when analyzed individually, firm size has a significant effect on audit fees. In contrast, financial risk, complexity, and auditor reputation do not have a significant effect on audit fees. Simultaneously, firm size, financial risk, complexity, and auditor reputation significantly influence audit fees by 46.2%, as indicated by the coefficient of determination (R²).